Robust effects of genetic background on responses to subarachnoid hemorrhage in mice. Issue 11 (November 2016) - D'Abbondanza, Josephine A; Ai, Jinglu; Lass, Elliot; Wan, Hoyee; Brathwaite, Shakira; Tso, Michael K; Lee, Charles; Marsden, Philip A; Macdonald, R Loch
Outcome varies among patients with subarachnoid hemorrhage but known prognostic factors explain only a small portion of the variation in outcome. We hypothesized that individual genetic variations influence brain and vascular responses to subarachnoid hemorrhage and investigated this using inbred strains of mice. Subarachnoid hemorrhage was induced in seven inbred and a chromosome 7 substitution strain of mouse. Cerebral blood flow, vasospasm of the middle cerebral artery, and brain injury were assessed. After 48 h of subarachnoid hemorrhage, mice showed significant middle cerebral artery vasospasm that correlated positively with reduction in cerebral blood flow at 45 min. Mice also had increased neuronal injury compared to sham controls; A/J and C57BL/6 J strains represented the most and least severe, respectively. However, brain injury did not correlate with cerebral blood flow reduction at 45 min or with vasospasm at 48 h. Chromosome 7 substitution did not influence the degree of vasospasm or brain injury. Our data suggested that mouse genetic background influences outcome of subarachnoid hemorrhage. Investigations into the genetic factors causing these inter-strain differences may provide insight into the etiology of the brain damage following subarachnoid hemorrhage. These findings also have implications for animal modeling of disease and suggest that genetic differences may also modulate outcome in other cardiovascular diseases.